Factors Affecting Callus Induction and Organogenesis in Saffron (Crocus sativus L.) (Plant Tissue Culture and Biotechnology, 2014)
Saffron (Crocus sativus L.) belongs to Iridaceae and is known an important native commercial plants in Iran for its high value of saffron. The best growth regulator composition for callus production from corms and sahoot regeneration from callus were determined. Saffron corms harvested from previous crops are generally used for future cropping cycles. However, this practice causes major yield losses due to the heavy attack by different pathogens. Availability of healthy disease free planting materials is of great importance for successful cultivation of saffron. By this investigation the best composition of growth regulators for callus production from corms and shoot regeneration from callus were determined. Callus induction of Crocus sativus L. was investigated by using different combinations NAA, 2, 4-D and TDZ, BA and Kn. The highest frequency of callus induction was observed in medium containing 2 mg/l 2, 4-D + 1 mg/l BA followed by 1 mg/l 2, 4-D + 0.15 mg/l Kn. However, in case of growth parameters such as diameter and the area of calli the best result was obtained in the medium supplemented with 2 mg/l 2, 4-D + 1 mg/l BA.  In some treatments, calli were transferred to organogenesis stage after two subcultures.  For sprouting of shoots transferred to medium containing 1 mg/l BAP and 1 mg/l NAA. Statistical analyses indicated that the treatment containing 5 mg/l NAA and 5 mg/l TDZ  proved to be the best growth regulator treatment for shoot regeneration from the saffron calli. Plant Tissue Cult. & Biotech. 24(1): 1-9, 2014 (June) D. O. I. http://dx.doi.org/10.3329/ptcb.v24i1.19184